2014
DOI: 10.1007/s00425-014-2041-2
|View full text |Cite
|
Sign up to set email alerts
|

Selection of candidate reference genes for real-time PCR studies in lettuce under abiotic stresses

Abstract: The process of selection and validation of reference genes is the first step in studies of gene expression by real-time quantitative polymerase chain reaction (RT-qPCR). The genome of lettuce, the most popular leaf vegetable cultivated worldwide, has recently been sequenced; therefore, suitable reference genes for reliable results in RT-qPCR analyses are required. In the present study, 17 candidate reference genes were selected, and their expression stability in lettuce leaves under drought, salt, heavy metal,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
84
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(98 citation statements)
references
References 49 publications
13
84
0
1
Order By: Relevance
“…For example, when evaluating the expression of PAL and HPPD genes in lettuce plants (Lactuca sativa L.), Borowski et al (2014) observed significant differences in the expression of these genes depending on both the reference gene and stress condition used. The results of this study confirm the importance of a specific choice of reference genes for transcript analyses by RT-qPCR.…”
Section: Discussionmentioning
confidence: 99%
“…For example, when evaluating the expression of PAL and HPPD genes in lettuce plants (Lactuca sativa L.), Borowski et al (2014) observed significant differences in the expression of these genes depending on both the reference gene and stress condition used. The results of this study confirm the importance of a specific choice of reference genes for transcript analyses by RT-qPCR.…”
Section: Discussionmentioning
confidence: 99%
“…RT-qPCR has become the most popular method for the quantification of transcript accumulation and must be preceded by validated normalization to prevent variations arising from non-biological events (Borowski et al, 2014). Questionable gene expression results occur when target genes are normalized against single reference genes without adequate justification and when non-validated reference genes are used (Bustin et al, 2009;Derveaux et al, 2010).…”
Section: Description and Expression Profiling Of Candidate Reference mentioning
confidence: 99%
“…The purpose of these reference genes is to normalize the variations in RNA quantity and quality (Ponton et al, 2011). This validation requires the most suitable reference gene to be chosen to normalize the results for each species and under each experimental condition (Borowski et al, 2014).…”
Section: Description and Expression Profiling Of Candidate Reference mentioning
confidence: 99%
See 2 more Smart Citations